Constructing the disk method formula for the volume obtained by revolving a curve around an axis with the help of CAS - Aktümen, Muharrem; Kabaca, Tolga (Teaching Mathematics and Computer Science, 2007)
Calculus concepts should have been taught in a carefully designed learning environment, because these concepts constitute a very important base for almost all applied sciences. The integral, one of the fundamental concepts of Calculus, has a wide application area. This paper focuses on constructing the disk method formula for the volume obtained by revolving a curve around an axis with the help of a CAS. In this study, a semi-structured interview was carried out. In this interview, we tried to construct the disk method formula. The levels of constructing the disk method formula in this study are: • Introducing the concept: evaluating the volume of an Egyptian pyramid. • Evaluating the volume of a cone obtained by revolution (using Maple worksheet). • Designing their own ring and evaluating its price (using Maplet). In this study, the interview has been presented as a dialog between teacher and students. When we look at feedback from students, we see that such a teaching method effects students in a positive way and causes them to gain conceptual understanding directed towards the concepts of approximation and volume.